Kajian Nilai Budaya ‘Etu’ dan Integrasinya dengan Pendidikan Jasmani Adaptif Pada Anak Berkebutuhan Khusus di Kabupaten Nagekeo NTT - Ot Bil Wilson Selan; Vinsensius Wangge; Timoteus Ajito (Departement of Mathematics Education, 2023)
One of the cultural heritages of the Indonesian people is the traditional Etu boxing tradition. Besides being full of various skills and dexterity for self-defense, Etu traditional boxing is also a test of virility and courage among young men in Nagekeo district which is rich in the traditions that surround it. The Etu traditional boxing sport is very rich in socio-cultural values and philosophical meaning. This research aims to find out, 1) the noble values contained in Etu, 2) describe the role of traditional elders/traditional figures in implementing Etu, 3) describe the formation of community character in Etu sports. in Nagekeo district, East Nusa Tenggara, and see the process of inheriting the traditional Etu boxing sport from generation to generation. This research uses a qualitative approach where data is obtained using Miles Matthew analysis. B and Huberman Michael, which consists of three stages, namely data reduction, data presentation, and ending with drawing conclusions. The research results show that Etu traditional boxing is not just a sport, but is full of value and meaning in people's lives. The process of inheriting Etu traditional boxing is also going well to date. The characters that can be formed from traditional Etu sports in adaptive physical education learning for autistic children are to improve motor and psychomotor skills, improve balance and coordination, and improve cognitive qualities, positive attitudes and emotional intelligence.